A life course perspective on working beyond retirement-results from a longitudinal study in the Netherlands - Astrid de Wind; Suzan van der Pas; Birgitte M. Blatter; Allard J. van der Beek (BMC, 2016)
Abstract Background There is a societal need that workers prolong their working lives. By adopting a life course perspective, this study aimed to investigate the influence of work motives and motivation, health, job characteristics, skills, and financial and social situation on working beyond retirement, and differences between 'on time' and 'off time' retirees (retirement age 65 and <65 years, respectively). Methods Retirees aged 57 to 67 years (N = 1,054) who participated in the Dutch Study on Transitions in Employment, Ability and Motivation were included in this study. Participants filled out a questionnaire in 2010, 2011, 2012, and 2013. Predictors of working beyond retirement were identified using logistic regression analyses, and stratified analyses were performed to investigate differences between 'off time' and 'on time' retirees. Results High work engagement (OR = 1.3), good physical health (OR = 1.8), poor financial situation (OR = 2.4), and voluntary work (OR = 1.5) predicted working beyond retirement. For 'off time' retirees, no financial possibility to retire early (OR = 1.8) and not having a partner (OR = 1.9) predicted working beyond retirement. 'On time' retirees reporting more support at work (OR = 0.7) and without the financial possibility to retire early (OR = 0.5), worked beyond retirement less often. Conclusions The results indicated that especially the motivation to work, physical health and the financial situation were the most relevant aspects with regard to working beyond retirement, which supports the idea that the principle of 'human agency' of the life course perspective is useful to understand factors that impact working beyond retirement. Most aspects of the life course principles of 'linked lives' and 'timing' seemed to be less relevant.